ANALYSIS OF THE UTILIZATION OF PRODUCTIVE ZAKAT AS A MEANS OF BUSINESS ASSISTANCE FOR MUSTAHIQ ASSISTED BY BAZNAS CIREBON CITY - Fauzi Rizky Bahari (Publikasi Indonesia, 2023)
The Covid-19 virus pandemic in Indonesia has resulted in an increase in the poverty rate in the community, the impact of the outbreak of the Covid-19 pandemic is very much felt in many countries, especially in Indonesia. Four sectors are most depressed due to the Covid-19 virus outbreak, namely households, MSMEs, corporations, and the financial sector. Productive zakat is one of the effective zakat distribution models in solving social problems, especially poverty alleviation. So productive zakat must be managed properly. The distribution of zakat should be prioritized to build productive businesses for zakat recipients in order to be able to generate income for mustahiq. In other words, the distribution of zakat must change from a consumptive pattern to a productive pattern.This study aims to analyze the productive zakat program in BAZNAS Cirebon city, analyze the implementation of productive zakat by the Cirebon city BAZNAS, and analyze the benefits of productive zakat on the welfare of mustahiq.This research uses a descriptive qualitative approach with the type of case study research, in which the researcher conducts an in-depth exploration of the program, events, processes, activities, of the Cirebon City BAZNAS employees and the mustahiq of the productive zakat program.The results of the study showed that BAZNAS Cirebon city maximized efforts in collecting and distributing zakat by using several strategies. In terms of collection, BAZNAS Cirebon city uses a socialization strategy through zakat fitrah and socialization through social media. In terms of distribution, BAZNAS Cirebon uses a strategy of utilizing zakat by creating social programs. There are also several problems at BAZNAS Cirebon city in carrying out community empowerment through the utilization of zakat or commonly called productive zakat, namely: Immature program planning, Lack of reliable companion human resources, Not yet established a sustainable empowerment cycle. The external problems of BAZNAS are: Low ZIS income to BAZNAS, Low awareness of zakat obligors, Low entrepreneurial spirit of mustahiq.